2004
DOI: 10.1159/000082295
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes of Cerebellar Tumors in Children

Abstract: Cerebellar tumors in childhood are generally associated with a favorable outcome if they are managed appropriately. 27 cases of pediatric cerebellar tumors, operated over a 7-year period, are presented. Histopathological diagnoses were as follows: pilocytic astrocytoma (48.2%); medulloblastoma (22.2%); ependymoma (18.5%); fibrillary astrocytoma grade III (3.7%); cystic oligodendroglioma (3.7%), and hemangioblastoma (3.7%). Microscopic gross total resection was achieved in 16 (59.3%) of 27 cases. The total remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 34 publications
1
13
0
2
Order By: Relevance
“…The causes are: postoperative edema of cerebellum, obstruction to CSF re-absorption due to subarachnoid hemorrhage, adhesion of the opening to the fourth ventricle and its surroundings, and etc. [7,8] Postoperative hydrocephalus is the most severe complication of the surgery for pediatric tumor of posterior cranial fossa and even endangers life if not properly treated. Therefore, soon after the surgery, ventriculoperitoneal shunt or ventriculostomy under neuroendoscope should be performed if circumstances allow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The causes are: postoperative edema of cerebellum, obstruction to CSF re-absorption due to subarachnoid hemorrhage, adhesion of the opening to the fourth ventricle and its surroundings, and etc. [7,8] Postoperative hydrocephalus is the most severe complication of the surgery for pediatric tumor of posterior cranial fossa and even endangers life if not properly treated. Therefore, soon after the surgery, ventriculoperitoneal shunt or ventriculostomy under neuroendoscope should be performed if circumstances allow.…”
Section: Discussionmentioning
confidence: 99%
“…For malignant pediatric tumor of posterior cranial fossa, treatment relies on complementary radiotherapy and/or chemotherapy on the basis of performing surgery [8] . Debate remains on the question of how to select complementary therapies which are suitable for the certain pathological types of the tumor [8][9][10] . We believed that therapy should be individualized, according to the age of the patients, the characteristics of tumors, surgical conditions, and tumor's sensitivity to radiotherapy and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, these data pertain to single tumor entities, such as medulloblastomas, brain stem tumors, or ependymomas. However, outcome data on mixed tumor case series have not been reported frequently, whereas for most centers treating children with brain tumors, these data may be more pertinent to compare to than the outcome data on single tumor entities, which are often derived from renowned, large pediatric neurosurgical centers, which are not readily accessible for most patients around the world [1, 3, 19, 22]. …”
Section: Objectivementioning
confidence: 99%
“…For example, the evaluation of extent of resection by neurosurgeons is notoriously inaccurate though other retrospective series have concluded that a gross total resection is associated with favorable survivals. 34,35 In addition, the small size of our study also limits our comments regarding treatment.…”
Section: Discussionmentioning
confidence: 89%